Tembilahan Islamic Center Dengan Pendekatan Arsitektur Hijau - S, Mira Dharma; Yusuf, Muhammad; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Everyday, the times continues to grow by leaps and bounds resulting in Muslims having failed in so many aspects of life, namely in the aspect of education, knowledge, political, economic, social, and art culture. One of the facility that can accommodate it is Islamic Center. Islamic Center is a balance place for Muslims with basic concepts are vertical and horizontal relationships of life, the vertical relationship, is the relationship between Muslims and Allah SWT and the horizontal relationship, is the relationship between one Muslim to the others. Environmental problems are also global problems nowadays. One of them is the issue of energy, an increase of energy deman due to the increasing numbers of houses, factories, and commercial and industry buildings. So, the Islamic Center uses the green architectural approach based on Hablum mina Allah and hablum mina annas. The concept of green architectural based on Hablum mina Allah poured in the form of green architectural principles based on the oracles of Allah SWT while the concept of green architectural based on Hablum mina annas poured in the green architectural principles for the human prosperity. Those principles are principles that can make us closer to God through nature, principles of sustainable and energy-efficient, the environment-friendly principles, and helping-each-other principles. By doing this green architectural approach based on Hablum mina Allah and Hablum mina annas, so well as the effect on the order of mass, mass, form, space in the facade, interior, exterior spaces, circulation and others. we can get the facility needs for Muslims i.e. mosque, mess, muiltifunction room, retail, restaurant, Islamic Consultation Center, Islamic Organization Center, school and Art Islamic Gallery. Keywords: Islamic Center, Hablum Mina Allah and Hablum Mina Annas, and Green Architectural.